A 1-D model of the nonlinear dynamics of the human lumbar intervertebral disc. (20th January 2017) - Marini, Giacomo; Huber, Gerd; Püschel, Klaus; Ferguson, Stephen J.
Abstract: Lumped parameter models of the spine have been developed to investigate its response to whole body vibration. However, these models assume the behaviour of the intervertebral disc to be linear-elastic. Recently, the authors have reported on the nonlinear dynamic behaviour of the human lumbar intervertebral disc. This response was shown to be dependent on the applied preload and amplitude of the stimuli. However, the mechanical properties of a standard linear elastic model are not dependent on the current deformation state of the system. The aim of this study was therefore to develop a model that is able to describe the axial, nonlinear quasi-static response and to predict the nonlinear dynamic characteristics of the disc. The ability to adapt the model to an individual disc's response was a specific focus of the study, with model validation performed against prior experimental data. The influence of the numerical parameters used in the simulations was investigated. The developed model exhibited an axial quasi-static and dynamic response, which agreed well with the corresponding experiments. However, the model needs further improvement to capture additional peculiar characteristics of the system dynamics, such as the change of mean point of oscillation exhibited by the specimens when oscillating in the region of nonlinear resonance. Reference time steps were identified for specific integration scheme. The study has demonstrated that taking into account the nonlinear-elastic behaviour typical of the intervertebral disc results in a predicted system oscillation much closer to the physiological response than that provided by linear-elastic models. For dynamic analysis, the use of standard linear-elastic models should be avoided, or restricted to study cases where the amplitude of the stimuli is relatively small. Abstract : Highlights: A 1-dof nonlinear lumped parameters model of the intervertebral disc is proposed. The model is validated against quasi-static and dynamic experiments. A nonlinear elastic model is required to predict nonlinear phenomena similar to those seen in the experiments. The dynamic responses predicted from a linear and a nonlinear elastic viscous model are compared. The numerical parameters and the approach to use the nonlinear elastic viscous model are provided.